2008
DOI: 10.1593/neo.08164
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MAP Kinase Signaling Through ERK5 But Not ERK1 Expression Is Associated with Lymph Node Metastases in Oral Squamous Cell Carcinoma (OSCC)

Abstract: In an attempt to further elucidate the pathomechanisms in oral squamous cell carcinoma (OSCC), gene expression profiling was performed using a whole-transcriptome chip that contains 35,035 gene-specific 70 mere oligonucleotides (Human OligoSet 4.0; Operon, Cologne, Germany) to a set of 35 primary OSCCs. Altogether, 7390 genes were found differentially expressed between OSCC tumor samples and oral mucosa. To characterize the major biologic processes in this tumor collection, MAPPFinder, a component of GenMAPP v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 45 publications
2
61
0
1
Order By: Relevance
“…Expression datasets of human cell line were excluded in the study. The included GEO datasets (GSE) are shown in Table 1 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%
“…Expression datasets of human cell line were excluded in the study. The included GEO datasets (GSE) are shown in Table 1 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%
“…To further define the potential role of candidate proto-oncogenes in initiation and progression of OSCC, a subsequent tissue mRNA expression analysis and a microarray analysis (TMA) applying fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) were performed for selected candidate genes. Combining DNA array technology with high throughput tumor analysis using tissue microarray technology allows the rapid assessment of overall prevalence of candidate oncogene aberrations in representative tumor series (Freier et al, 2006;Sticht et al, 2008). In this respect, the actual prevalence of individual candidate gene copy number gains and consecutive high protein expression in a representative collection of 308 OSCC specimen was determined.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ERK5 signalling has also been implicated in human mesothelioma cell proliferation, migration, invasion, and resistance to therapy [100] and, more importantly, has been suggested as a potential beneficial therapeutic target for the development of treatment strategies in patients with malignant mesothelioma [100]. Lastly, ERK5 overexpression has also been implicated in head and neck squamous carcinoma, and associated with advanced tumour stage and lymph node metastasis [101]. In fact, subsequent studies demonstrated that miRNA-143 upregulation led to the inhibition of cell migration and invasion [102], possibly related to ERK5 targeting.…”
Section: Other Cancer Typesmentioning
confidence: 99%